MULTIETHNIC NEIGHBORHOODS ON THE GROUND: Resources, Constraints, and Sense of Community. (26th October 2016) - Walton, Emily; Hardebeck, Mae
Abstract: As our nation and our neighborhoods increasingly diversify, we should understand how to sustain integrated communities that are equally beneficial for all residents. Though our policies encourage diversity as a theoretical social good, we actually know little about what happens on the ground in multiethnic neighborhoods. We conduct a comparative case study of the only two Boston neighborhoods to have maintained at least 10% representation of four racial and ethnic groups over the past two decades. Using survey data and ethnographic field observations, we examine residents' experiences in these two consistently multiethnic, yet very different, neighborhoods. We find that neighborhood socioeconomic and racial inequality and disadvantage matter for residents' access to neighborhood resources and constraints, and their perceptions of sense of community. Notably, in the highly unequal South End, Whites and homeowners have greater access to amenities and have higher perceptions of sense of community in comparison to racial and ethnic minorities and renters. Socioeconomic disadvantage matters in Fields Corner, as evidenced by lower overall perceptions of sense of community and greater exposure to safety concerns among all groups in this neighborhood compared to residents of the South End. In the end, we argue that having multiple groups simply sharing neighborhood space over a stable period is not enough to overcome the social problems associated with residential segregation and isolation. In order to support equitable neighborhood integration amid the changing face of diversity, we should take cues from "diverse by direction" neighborhood models that include active organization and coalition building among dissimilar racial and ethnic groups.